Crateriform and ulcerated lesions of nodular lepromatous leprosy masquerading as histoid Hansen’s disease - Makudapathy, Siddharth; Kuppu, Sriram Chinnathambi (International Journal of Research in Dermatology, 2026)
Nodular lepromatous leprosy (LL) classically presents with diffuse infiltration, nodules, and plaques. However, unusual morphologies may lead to diagnostic confusion, particularly with histoid Hansen’s disease. We report a rare presentation of nodular lepromatous leprosy manifesting as crateriform and ulcerated papules and plaques, clinically simulating histoid leprosy. Detailed clinical evaluation, histopathology, and slit-skin smear examination aided in establishing the correct diagnosis. This case highlights the importance of recognizing atypical cutaneous manifestations of leprosy to avoid misclassification and ensure appropriate management.